Propanephosphonic Acid Anhydride (T3P®) - A Benign Reagent for Diverse Applications Inclusive of Large-Scale Synthesis - null; Vishwanatha, T. M.; Panguluri, Nageswara Rao; Sureshbabu, Vommina V. (Synthesis, 2013)
Propanephosphonic acid anhydride (T3P®) is a prevailing coupling and dehydrating agent with many desirable properties which render it a reagent of choice for a plethora of reactions and, befittingly, its application in organic synthesis is rapidly increasing. Since its introduction as a peptide coupling agent in 1980, the realm of applications of T3P has expanded. Currently its use is found in a broad range of reactions, including condensation, functional group transformation, heterocycles preparation, rearrangements, and catalysis. It offers several advantages over traditional reagents, such as high yield, chemical and optical purity, broad functional group tolerance and easy work-up. The reagent is attractive for large-scale synthesis as well, and particularly so for multi-kilogram scale preparations of drug molecules. This article reviews the hitherto reported applications of T3P as a reagent in organic synthesis. Focus is also placed on the use of T3P for large-scale synthesis. 1 Introduction2 Structure and Preparation3 T3P in Peptide Chemistry 3.1 As a Coupling Agent3.2 Synthesis of Amino Acid Derivatives and Peptidomimetics4 General Applications4.1 As a Carboxylic Acid Activator4.2 As a Dehydrating Agent4.3 Synthesis of Heterocycles4.4 Oxidation Reactions4.5 Carbon–Carbon Bond Formation4.6 Rearrangement Reactions4.7 Synthesis of Drugs on Laboratory and Large Scales5 Recent Applications6 Conclusion
Keywords: coupling; racemization; rearrangement; large-scale synthesis